Pandemic Management in a Pediatric Hospital. (April 2013) - Ratnapalan, Savithiri; Martimianakis, Maria Athina (Tina); Cohen-Silver, Justine H.; Minnes, Bruce; MacGregor, Daune; Allen, Upton; Richardson, Susan E.; Friedman, Jeremy N.; Bruce-Barrett, Cindy; Haj-Assaad, Lutfi; Noordermeer, Judy; Daneman, Denis
Objectives . To describe our experiences in the management of the second wave of influenza A H1N1 (pH1N1) pandemic in a tertiary-care children's hospital. Methods . An autoethnographic study of the pandemic planning and management committee members involved in managing the second wave of pH1N1 was conducted. Results . Staffing, surge capacity, communications and emergency operations planning by adding leaders of frontline workers and other key operational roles to the incident management team, and creating a tactical response team emerged as important factors in pandemic management in our hospital. The emergency department visits increased by 50%, necessitating increased staffing of the emergency department. Communications using existing chains of command had to be used to reach frontline staff during the pandemic. Conclusions . Incident management teams managing pandemics and other disasters have to be dynamic and create tactical teams to ensure implementation and facilitate bidirectional communication with frontline workers.